Impact of rainfall change on the agro-ecological regions of Sri Lanka - Muthuwatta, Lal P.; Liyanage, Panni Kankanamlage Nirosha Chandani (2013)
Changes in future rainfall distribution for the agro-ecological regions of Sri Lanka were analyzed. The baseline period to compare future predictions was taken as 1970 to 2000. Downscaled climate change prediction grids were extracted from the UK Hadley Centre for Climate Prediction and Research Model (HadCM3). These grids were extracted for 2050. In the baseline period 76 stations of147 showed decreasing trends in annual rainfall and 71 increasing trends. Thirty six of the 76 stations showing a decrease were in the wet zone. In the intermediate zone 17 stations showed increasing trends and in the dry zone 34 stations indicated increasing trends. Mean annual rainfall (MAR) for the baseline period for the whole country was 2094 mm/year while the projected value for 2050 is 2249 mm/year. The increase of MAR over Sri Lanka by 2050 compared to the baseline period is about 7%. The comparison of rainfall between the baseline period and 2050 showed that some areas of the dry zone will receive MAR of more than 1750 mm and could be classified and included into the intermediate zone by 2050. Further, the increase of MAR for 11 agroecological regions goes beyond the variability observed in the baseline data set.